Education and its effect on monetary poverty of households in Peru - Quispe Mamani, Julio Cesar; Cáceres Quenta, Rolando; Guevara Mamani, Marcial (Frontiers in Education, 2024)
IntroductionThe objective of this research was to determine the effect of education on poverty in Peruvian households, in the period 2022.MethodsFor which the quantitative approach was considered, of a non-experimental research type, with a descriptive correlational design, considering the information collected in the National Household Survey (ENAHO); the logit-binomial logistic regression model was used to measure the effect of the variables expenditure on education, monthly economic income, years of schooling, the mother tongue of the head of the household, age of the head of the household, marital status of the head of the household, gender of the head of the household, and area of residence, on the probability of being poor, according to the poverty line established by the INEI.Results and discussionAccording to the results obtained, expenditure on education, monthly economic income, years of schooling, and area of residence explain the probability of being poor in a negative way, while the mother tongue of the head of the household, the age of the head of the household, the marital status of the head of the household, and the gender of the head of the household explain the probability of being poor in a positive way. Therefore, it was determined that there is a significant effect of education on whether households in Peru are considered poor or not.